Approaches to the application of the analytic hierarchy process in order to make a decision by the head of the border control unit - M. N. Sorokin; D. S. Rabenka (Системный анализ и прикладная информатика)
The head of the border control unit faces the need to make the decision on the protection of the state border at the border crossing point every day. Decision-making on the protection of the state border is a complex multifactorial process with the variability of possible final values. The article discusses the possibility of using the hierarchy analysis method for the decision-making process by the head of the border control unit. In order to make an optimal decision, using the method of analyzing hierarchies, it is necessary to decompose the known factors into indicators that directly affect the protection of the state border and the situation at the border crossing point. Decomposition of factors into indicators was carried out by the method of expert assessment, the disadvantage of which is the possible subjectivity of expert judgments. To obtain a sufficient number of qualitative judgments when choosing indicators of factors that directly affect the protection of the state border, the authors propose a method for determining the required number of experts when conducting expert assessments. Based on the results obtained, the allowable size of the expert group was 18 specialists involved in assessing the research problem. The research indicates that the involvement of experts in excess of the specified number leads to the presentation by them of insignificant for decision-making or repeated judgments. In order to achieve the best results, substantiate the proposal of all possible optimal indicators of factors that directly affect the protection of the state border, a categorical selection of experts in the direction of protecting the state border at the border crossing point has been established.